(untitled) (Rajshahi University Journal of Life & Earth and Agricultural Sciences, 2015)
The experiment was conducted at the Agronomy Field laboratory, Department of Agronomy and Agricultural Extension, University of Rajshahi to study the yield and yield components of wheat as affected by phosphorus fertilization. The experiment consisted of two factors i.e. (i) three wheat varieties viz., Shatabdi, Bijoy and Prodip and (ii) five levels of phosphorus viz. 0, 30, 60, 90, 120 kg P2O5 ha-1. A RCBD design was used for the experiment with three replications. The effect of variety was significant on all the yield components and yield except plant height. Prodip gave the highest grain yield (3.67 t ha-1) followed by Bijoy (3.45 t ha-1) and Shatabdi (3.28 t ha-1). Yield and yield components of wheat were significantly influenced by different levels of phosphorus. The highest grain yield (4.47 t ha-1) was recorded from P4 (120 kg P2O5 ha-1) and the lowest one (2.43 t ha-1) from the control treatment. The highest grain yield (4.80 t ha-1) was obtained from Prodip at 120 kg P2O5 ha-1 and the lowest one (2.3 t ha-1) was found in Shatabdi at control treatment. The results suggest that the combination of V3P4 (Prodip with 120 kg P2O5 ha-1) is the best for obtaining higher yield of wheat.